Role of ultrasound in reducing complication during primary trocar insertion in laparoscopic surgery: prospective observational study - Dhama, Vandana; Dhama, Vipin; Chaudhary, Rachna; Singh, Shakun; Aafrin, Saba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Patients presenting to Gynecology OPD at LLRM Medical College, Meerut, UP, India for benign laparoscopic surgery from June 2016 to May 2017 were included in the study. A total of 130 women completed the study of which 30 had history of previous abdominal surgery and 100 had no history of previous abdominal surgery. The ability of the visceral slide test to detect periumbilical adhesions was compared with laparoscopic detection of adhesions. Methods: Patients fulfilling inclusion and exclusion criteria and preanaesthetic clearance were subjected to office based Visceral Slide test using high frequency ultrasound probe (7.5 MHz) in the sagittal plane at the level of umbilicus. Distance between the skin and posterior rectus sheath was measured. Diagnostic accuracy of visceral slide test and mean time taken to perform the test was noted. Results: On laparoscopy 4 women had periumbilical adhesions while 24 women in the total sample had adhesions elsewhere in the abdominal cavity. The visceral slide test had a sensitivity of 75%, specificity of 98%, positive predictive value of 75% and negative predictive value of 99%. The diagnostic accuracy of the test is 97%. The median time to perform the examination was 1.69 minutes. Conclusions: The visceral slide technique was convenient and rapid to perform, and reliably identified adhesions in the periumbilical area.